2023
DOI: 10.21203/rs.3.rs-2626008/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Square-Wave Voltammetry of Human Blood Serum

Abstract: A study on voltammetric analysis of whole blood serum is presented using advanced square-wave voltammetry at an edge plane pyrolytic graphite electrode. The results demonstrate that even in a complex medium like human blood serum, electrochemical characterization can be achieved through the use of advanced voltammetric techniques in conjunction with an appropriate commercially available electrode, such as the edge plane pyrolytic graphite electrode, which boasts superior electrocatalytic properties. Without un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, the low selectivity of voltammetry biosensors in complex media (i.e., blood serum) poses a significant challenge. This is particularly relevant due to the presence of multiple redox-active species and the sensing mechanism employed by these biosensor structures [79]. Besides, the size and amount of nanostructures have significant effects on the sensitivity of biosensors, which can affect the sensor simplicity and reproducibility.…”
Section: A Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the low selectivity of voltammetry biosensors in complex media (i.e., blood serum) poses a significant challenge. This is particularly relevant due to the presence of multiple redox-active species and the sensing mechanism employed by these biosensor structures [79]. Besides, the size and amount of nanostructures have significant effects on the sensitivity of biosensors, which can affect the sensor simplicity and reproducibility.…”
Section: A Electrochemical Biosensorsmentioning
confidence: 99%
“…Besides, the size and amount of nanostructures have significant effects on the sensitivity of biosensors, which can affect the sensor simplicity and reproducibility. Recently, a study has shown that using edge-plane pyrolytic graphite electrodes relying on an advanced SWV method can address some issues for electrochemically characterizing human serum without pre-treatment of the samples or surface modification [79]. In this spectroscopy-like method, the role of choosing electrodes and parameter changes in SW pulses has been studied under different serum samples.…”
Section: A Electrochemical Biosensorsmentioning
confidence: 99%